Exergy analysis of a solar photovoltaic module - Serrano-Casares, Francisco Víctor; Zaragoza, E. (My University, 2016)
PV energy is the direct conversion of solar radiation into electricity. In this paper, an analysis of the influence of parameters such as global irradiance or temperature in the performance of a PV installation has been carried out. A PV module was installed in a building at the University of Málaga, and these parameters were experimentally determined for different days and different conditions of irradiance and temperature. Moreover, IV curves were obtained under these conditions to know the open-circuit voltage and the short-circuit current of the module. With this information, and using the first law of thermodynamics, an energy analysis was performed to determine the energy efficiency of the installation. Similarly, using the second law of thermodynamics, an exergy analysis is used to obtain the exergy efficiency. The results show that the energy efficiency varies between 10% and 12% and the exergy efficiency between 14% and 17%. It was concluded that the exergy analysis is more suitable for studying the performance, and that only electric exergy must be considered as useful exergy. This exergy efficiency can be improved if heat is removed from the PV module surface, and an optimal temperature is reached.
Keywords: Energia solar; PV module; Exergy efficiency; Optimal temperature